2001
DOI: 10.1177/00912700122010933
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam Disposition in Patients Undergoing Continuous Venovenous Hemodialysis

Abstract: The aim of the study was to investigate the pharmacokinetics and removal of midazolam and unconjugated and glucuronidated 1-hydroxy-midazolam in 4 intensive care patients on continuous venovenous hemodialysis. Plasma midazolam and its metabolites were assessed by HPLC from blood samples collected during continuous infusion and after the end of infusion. Additional samples from the arterial and venous bloodlines and ultrafiltrate were drawn to calculate sieving coefficient and clearance of ultrafiltration. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 6 publications
3
16
1
Order By: Relevance
“…Prolonged sedation additionally caused by an accumulation of conjugated 1-hydroxymidazolam was also observed in septic shock patients with severe renal failure [ 26 , 27 ]. Bolon et al [ 28 ] showed that in such cases, dialysis is rather effective in eliminating the conjugated metabolite than midazolam itself. Therefore, for patients needing dialysis, liver function plays a key role in midazolam clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged sedation additionally caused by an accumulation of conjugated 1-hydroxymidazolam was also observed in septic shock patients with severe renal failure [ 26 , 27 ]. Bolon et al [ 28 ] showed that in such cases, dialysis is rather effective in eliminating the conjugated metabolite than midazolam itself. Therefore, for patients needing dialysis, liver function plays a key role in midazolam clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Step 6 Patients worldwide have been sedated in intensive care units (ICUs) for decades; however, many controversies still surround the issue of how to monitor for sedation in the ICU setting. 1,2 The main aim of sedation in the critically ill patient is to make the patient calm, cooperative, and able to communicate by providing relief from agitation, anxiety, and pain. 3,4 Benzodiazepines have a high affinity for ␥aminobutyric acid (GABA) receptors.…”
Section: Discussionmentioning
confidence: 99%
“…5 Midazolam is a shortacting benzodiazepine with a rapid onset of action; it has been widely used as a sedative in mechanically ventilated patients since its introduction to United States and Canadian markets in 1986 and 1988, respectively. [2][3][4][5][6][7] The half-life of midazolam is approximately 3 hours; however, there is wide interindividual variability in both healthy individuals and critically ill patients. 7,8 Midazolam undergoes hydroxylation by hepatic cytochrome P450 (CYP) isoenzyme 3A4 to form three metabolites, which are cleared renally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHARMACOTHERAPY Volume 40, Number 12, 2020 observed because of a widely variable half-life due to redistribution into adipose tissue and an active metabolite that is renally eliminated and only partially cleared by renal replacement therapies. [55][56][57] Midazolam should be avoided or limited to intermittent dosing in these at-risk populations unless no other options exist. 58…”
mentioning
confidence: 99%